2021
DOI: 10.1186/s12913-021-06142-8
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the rationalization of surgical instrument trays: scoping review and research agenda

Abstract: Background Surgical Tray Rationalization (STR) consists of a systematic reduction in the number of surgical instruments to perform specific procedures without compromising patient safety while reducing losses in the sterilization and assembly of trays. STR is one example of initiatives to improve process performance that have been widely reported in industrial settings but only recently have gained popularity in healthcare organizations. Methods We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…It is noticeable that the role of health professionals in the CSSD goes beyond routine and repetitive work, requiring specific training for qualification in the development of specific skills to work in this sector [ 11 ]. This finding is in agreement with the study by Santos et al, which points out that the elimination of unnecessary or redundant instruments in surgical trays can save time, require less operational effort, and bring lower costs to the CSSD, without compromising the surgical procedure and the health of patients [ 24 ]. Therefore, simplifying surgical instruments can also significantly reduce sterilization time, decrease ergonomic risks, and lower instrument acquisition costs.…”
Section: Discussionsupporting
confidence: 92%
“…It is noticeable that the role of health professionals in the CSSD goes beyond routine and repetitive work, requiring specific training for qualification in the development of specific skills to work in this sector [ 11 ]. This finding is in agreement with the study by Santos et al, which points out that the elimination of unnecessary or redundant instruments in surgical trays can save time, require less operational effort, and bring lower costs to the CSSD, without compromising the surgical procedure and the health of patients [ 24 ]. Therefore, simplifying surgical instruments can also significantly reduce sterilization time, decrease ergonomic risks, and lower instrument acquisition costs.…”
Section: Discussionsupporting
confidence: 92%
“…The first one applies RFID (radio-frequency identification) for surgical instruments to control the quality of surgical tray assembly and instrument traceability. Trays with missing instruments are a recurrent problem in surgical theaters [ 175 ]; an LH project to adopt electronic Poka–Yokes (mistake proofing) at the final stage of tray assembly would help to address the problem. The second one uses biomedical sensors connected to the IoT to track inward patients’ vital signals, activate rapid-response teams, and reduce the time to assist patients in critical condition.…”
Section: Future Researchmentioning
confidence: 99%
“…Four literature reviews relevant to the scope of the current work were identified (Table 1 ). In particular, Dos Santos and colleagues [ 6 ] sought to understand the main techniques and approaches in the rationalising of surgical sets, the impact on financial and operational performance, and the knowledge gaps towards which research should be directed. The review identified many studies reporting signs of improved performance both operationally , concerning set assembly, OR management and ergonomics, and efficiently in terms of washing and sterilisation processes, repair, purchasing, set-up and professional education.…”
Section: Resultsmentioning
confidence: 99%